2021
DOI: 10.3390/healthcare9060686
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Support and Morbidities on Self-Rated Health among Migrant Elderly Following Children to Jinan, China

Abstract: Social support has been demonstrated to be associated with the health status of old adults, but no study has clarified the relationship between social support, morbidities and self-rated health among the migrant elderly following children (MEFC) to new cities. This study aimed to explore the effect of social support and morbidities on self-rated health among MEFC to Jinan, China. A total of 656 MEFC were included in this study by using multi-stage cluster random sampling. Social support was measured by the Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The majority of MOC in the survey sample lived with their families, so family support and care may have led to higher levels of health and life satisfaction, similar to the results of previous studies [ 60 , 61 ]. Our study was similar to previous studies which also found the majority of MOC have a moderate level of social support [ 7 ]. This may be due to the fact that the subjects of this survey were MOC who mostly from rural areas and whose social support network in the city has not been fully constructed [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The majority of MOC in the survey sample lived with their families, so family support and care may have led to higher levels of health and life satisfaction, similar to the results of previous studies [ 60 , 61 ]. Our study was similar to previous studies which also found the majority of MOC have a moderate level of social support [ 7 ]. This may be due to the fact that the subjects of this survey were MOC who mostly from rural areas and whose social support network in the city has not been fully constructed [ 62 ].…”
Section: Discussionsupporting
confidence: 92%
“…For example, older migrants may have language barriers that lead to poor communication with locals, which affected their social interactions and ultimately have an impact on their social support [ 6 ]. Therefore, the health of the MOC was an issue of social concern [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey collected sociodemographic information from the participants, including age, gender, marital status, hukou (38), education level (39), duration in Jinan, migration scale (40), migration space range (33), income (41,42), etc. Hukou is a household registration system used in China, with individuals being assigned rural or urban hukou based on their place of birth and lineage (Rural = 0, Urban = 1).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 99%
“…Due to the problems in the positioning of functions, operational mechanisms and resource allocation of public elderly institutions, the development of public elderly institutions is not dynamic enough ( 18 , 19 ). Social support has been shown to be related to the health status of elderly people, with living with family members more likely to have higher levels of self-rated health ( 20 ). The impact of social support on the mental health of urban and rural elderly people is markedly different, with social support having a significant impact on the mental health of urban elderly people but not rural elderly people ( 21 ), and the most important factor limiting healthy aging in China's rural empty nesters is not physical health but social participation ( 22 ).…”
Section: Introductionmentioning
confidence: 99%